Siege of Vienna on 11 May 1809 - Gerasch, Franz, 1826-after 1893 (engraver):::Creator::::::::::::; Hoechle, Johann Nepomuk, 1790-1835 (artist):::Contributor:::::::::::: (Johann Rauh, 2021)
Lithograph of the siege of Vienna on 11 May 1809 by Gerasch after Hoechle, printed by Rauh.